EPIDEMIOLOGICAL CHARACTERISTICS OF PNEUMONIA WITH H. INFLUENZAE ISOLATION FROM PHARYNGEAL OUTBREAK AT HAI PHONG CHILDREN'S HOSPITAL IN 2022 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and subclinical characteristics of Haemophilus influenzae (HI) pneumonia and the antibiotic resistance profiles of the causative bacteria at the Children's Hospital in 2022.Subjects and Methods: A descriptive study was conducted on 162 children aged
Keywords: pneumonia, children, antibiotic resistance, H. influenzae